Membangun Super Enkripsi untuk Mengamankan Pesan - Agustina, Laura; Sujarwo, Imam; Khudzaifah, Muhammad (Jurnal Riset Mahasiswa Matematika, 2023)
The issue of message security or an information is very important. A science that studies about securing the confidentiality of messages using passwords is called cryptography. To enhance security, two algorithms are combined to secure messages. Super encryption is a concept that uses a combination of two or more substitution and permutation (transposition) cryptography techniques to obtain an algorithm that is more difficult to crack. The first thing to do is to encrypt the message using a substitution technique (Cipher Substitution), then re-encrypt it using a permutation technique (Cipher Transposition). In this study, two cryptographic algorithms will be combined to build super encryption using the Vigenere Cipher and Bifid Cipher algorithms to secure messages. The message encryption process is using the Vigenere Cipher algorithm for the first encryption process, then continued using the Bifid Cipher algorithm for the second encryption process. The encryption process is done the other way around, starting from the back of the encryption process. The combination of these two algorithms results in more secure message security.